High resolution DNA melting analysis: an application for prenatal control of alpha-thalassemia - Sirichotiyakul S. (2014)
To report the use of real-time gap-PCR using SYTO9 with high-resolution melting analysis (HRMA) in prenatal diagnosis of alpha-thalassemia 1.